Difference between revisions of "Boolean Algebra"

From TRCCompSci - AQA Computer Science
Jump to: navigation, search
(AND Identities)
(Redundancy Law)
Line 74: Line 74:
  
 
==Redundancy Law==
 
==Redundancy Law==
<math> \overline{A} = \overline{A} </math>
+
Law 1 :
or
+
<math> A + A \overline{B} = A + B </math>
<math> \overline{\overline{A}} = A </math>
+
 
 +
Proof :
 +
 
 +
<math>= A + A \overline{B} \\
 +
= (A + \overline{A})(A + B) \\
 +
= 1 . (A + B) \\
 +
= A + B </math>
 +
 
 +
 
 +
Law 2:
 +
<math> A.(\overline{A} + B) = A.B</math>
 +
 
 +
Proof :
 +
 
 +
<math>= A.(\overline{A} + B) \\
 +
= A.\overline{A} + A.B \\
 +
= 0 + A.B \\
 +
= A.B </math>
 +
 
  
 
==Identity Law==
 
==Identity Law==

Revision as of 09:40, 8 May 2018

Any equation must be within the <math> </math> tags. For Boolean alegbra the main issue is how to negate a term like:

¯a or ¯¯a+b

this can be done by adding the following around any term you wish to negate.:

<math> \overline{} </math>  

¯a

is

 <math> \overline{a} </math>

¯¯a+b

is

 <math> \overline{\overline{a}+b} </math>.

Identities

AND Identities

A=A

This equation means that the output is determined by the value of A. So if A =0, The output is 0, and vice versa.

0.A=0

Because there is a 0 in this equation, the output of this will always be 0 regardless of the value of A.

A.A=A

The output is determined by A alone in this equation. This can be simplified to just "A".

A.¯A=0

Here the output will be 0, regardless of A's value. A would have to be 1 and 0 for the output to be 1. This means we can simplify this to just 0.

OR Identities

0+A=A

If 0 or A goes in, A is the output

1+A=1

If 1 or A goes in, 1 is the output

¯A+1=1

If NOT A or 1 goes in, the output is 1

¯A+A=1

If NOT A or A goes in, the output is 1

Laws

Commutative Law

The Commutative Law is where equations are the same no matter what way around the letters are written. For example A+B=B+A or A.B=B.A

Laws

Associate Law

Distributive Law

The distributive law is these two equations.

A.(B+C)=A.B+A.C

A+(B.C)=(A+B).(A+C)

Redundancy Law

Law 1 : A+A¯B=A+B

Proof :

=A+A¯B=(A+¯A)(A+B)=1.(A+B)=A+B


Law 2: A.(¯A+B)=A.B

Proof :

=A.(¯A+B)=A.¯A+A.B=0+A.B=A.B


Identity Law

A+A=A

Negation Law

Equations

Solving equations is a matter of applying the laws of boolean algrebra, followed by any of the identities you can find:

Example 1

Example 2

Example 3

Example 4

Example 5

Example 6

Example 7